Implementation of self-tuning controllers - Warwick, Kevin 1954- (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
The first chapter of this book not only provides an overview of the scope and generality provided by self-tuning control schemes, but also indicates where such a scheme might be of benefit and how it complements and augments other control techniques. Chapters 2-5 discuss the basic ideas behind self-tuning control techniques; identification/ parameter estimation (chapter 2), optimal controller design (chapter 3), numerical considerations (chapter 4) and simplified methods (chapter 5). Chapters 6-9 discuss advances in the framework employed for self-tuning control; the delta operator (chapter 6), continuous-time control (chapter 7), software aspects (chapter 8) and predictive control (chapter 9). Chapters 10-13 are concerned with detailed application examples of; predictive control (chapter 10), PIP control (chapter 11), LQG optimal control (chapter 12) and various SISO/MIMO case studies (chapter 13).